THE PROBLEM OF SOCIAL RESPONSIBILITY IN THE "MAN-NATURE" SYSTEM - Ordenov, Serhii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Awareness of the planetary nature of the crisis in the system "man - nature" requires humanity to find new ways out of the problematic situation associated with uncontrolled use of nature. The aim of the article is to study from the standpoint of the social philosophy the specifics of social responsibility in the system of "man-nature". Research methods. The study used a dialectical method, as well as systemic and axiological approaches, which contributed to an in-depth understanding of social responsibility in the "man-nature" system. Research results. The article emphasizes the deepening of the ecological crisis in the context of globalization. Emphasis is placed on the fact that in global conditions, social responsibility in the "man-nature" system is related to the safety of nature and is aimed at achieving optimal interaction between society and nature. As the whole biosphere becomes an object of social responsibility in modern times, humanity is becoming a collective subject of responsibility, which requires the formation of special ecocentric initiative forms of personal responsibility, based on the principles of environmental imperative. Discussion. In the context of social responsibility in the "man-nature" system, the environmental factor must become decisive because it is a necessary condition for the preservation of natural diversity and restoration of the environment. Conclusion. The transition of a globalized society to a new phase of development requires a rethinking of understanding of nature and society, as well as the role and place of the man himself, the impact of his activities and behavior on the environmental situation in the world. Awareness of the planetary nature of the crisis in the "man-nature" system makes humanity find new ways out of the problematic situation associated with uncontrolled use of nature.